2002
DOI: 10.1002/sce.10009
|View full text |Cite
|
Sign up to set email alerts
|

The case of Carla: Dilemmas of helping all students to understand science

Abstract: This paper tells the story of four sixth-grade students, of mixed race and social class, who worked together in a small group. All four students were intrigued as they experimented with colored solutions of different densities. They all wanted to share ideas about the techniques they had used, the observations they had made, and the patterns they had seen. They all wanted to understand why the colored solutions acted as they did. In spite of these common interests, they often failed to achieve intersubjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 24 publications
0
28
1
Order By: Relevance
“…For each of the categories, the European-American students in the small science groups attained roles more frequently than their African-American counterparts who were, on average, comparable in academic performance and in spatial ability. While cognitive gains were not measured and reported in this investigation, previous studies suggested that those who do not participate do not learn as much as those who do (Bianchini, 1997;Kurth et al, 2002;Richmond & Striley, 1996); consequently, the results of this study may provide incidental insight upon the existing achievement disparities among European-American and African-American students. From the perspective of race, particularly whiteness in the USA, the researchers expected the aforementioned patterns in role attainment by European-American and African-American students in the small, racially mixed science groups.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…For each of the categories, the European-American students in the small science groups attained roles more frequently than their African-American counterparts who were, on average, comparable in academic performance and in spatial ability. While cognitive gains were not measured and reported in this investigation, previous studies suggested that those who do not participate do not learn as much as those who do (Bianchini, 1997;Kurth et al, 2002;Richmond & Striley, 1996); consequently, the results of this study may provide incidental insight upon the existing achievement disparities among European-American and African-American students. From the perspective of race, particularly whiteness in the USA, the researchers expected the aforementioned patterns in role attainment by European-American and African-American students in the small, racially mixed science groups.…”
Section: Discussioncontrasting
confidence: 46%
“…When the researchers viewed Carla's interactions within another group at a later time, the quality of Carla's contributions were significantly less than those she provided in the first group and the roles she assumed were far less challenging. This study continues the line of investigation presented in the Kurth et al (2002) case study and examines occurrences within small groups with regard to race.…”
Section: Overview Of the Literaturementioning
confidence: 92%
See 1 more Smart Citation
“…The Science Center was perceived as a gateway experience to future success. Given that there is evidence that traditional classroom practices have been found to privilege majority and upper income children (Cobern & Aikenhead, 1998; Kurth, Anderson, & Palincsar, 2002; Lee & Fradd, 1998; Moje, Collazo, Carillo, & Marx, 2001), these findings are particularly interesting and encouraging and worth further study; particularly given the dearth of confirmatory data in the literature.…”
Section: Discussionmentioning
confidence: 77%
“…This complex collaborative work presents social interaction challenges such as weighing opinions and keeping track of alternatives proposed by all group members, ensuring participation from all group members, and learning to offer and receive critiques (Coleman, 1998;Webb & Palincsar, 1996). The success of group work can be compromised by difficulties in these social interactions (Barron, 2003;Kurth, Anderson, & Palincsar, 2002).…”
Section: Unfamiliar Social Interaction Practicesmentioning
confidence: 99%